Production of viral antigens in culture fluid of C6/36 mosquito cell line infected with dengue type 4 virus strains isolated from patients with different clinical severities - C. Chanyasanha (2018)
Viral antigen production was examined in the culture fluid of Aedes albopictus clone C6/36 cell line incubated at 28°C and 37°C after infection with four strains of dengue type 4 (DEN-4) virus which were isolated from patients with different clinical severities. During the observation period from day 1 to day 18, the number of infected cells at each day for all four strains did not show any significant difference (P >0.05). Antigen production as determined by the hemagglutination (HA) test and sandwich enzyme linked immunosorbent assay (ELISA) was higher at 28°C than at 37°C for all four DEN-4 virus strains examined. The amount of viral antigen produced was highest for CT93-74 strain (dengue hemorrhagic fever syndrome (DHF) grade II) and was significantly different in comparison to other strains (P <0.001). This strain was followed by CT93-158 and CT93-129 strains (both of DHF grade I), and CT93-77 strain (dengue fever (DF)). The viral antigen production was apparently proportional to the clinical severity of the patient from whom the virus was isolated. These results show that CT93-74 strain could be used to produce DEN-4 virus antigen of sufficiently high titer in the C6/36 cell culture instead of classical extraction of this antigen from suckling mouse brains.